A comparison of the accuracy of peritoneoscopy and liver biopsy in the diagnosis of cirrhosis. Issue 10 (October 1974) - Bruguera, M.; Bordas, J. M.; Mas, P.; Rodes, J.
Abstract : The accuracy of peritoneoscopy and liver biopsy in the diagnosis of hepatic cirrhosis was compared in 473 consecutive patients submitted to both procedures. One hundred and fifty-two of them had cirrhosis diagnosed by one or both methods. There was 73% agreement between the two procedures. `Apparent' false-negative results were 17·7% for peritoneoscopy and 9·3% for liver biopsy. The incidence of false-negative results in the diagnosis of cirrhosis can be reduced by combining both procedures.